An intervention to decrease burnout and increase retention of early career nurses: a mixed methods study of acceptability and feasibility - Judy Brook; Leanne M. Aitken; Julie-Ann MacLaren; Debra Salmon (BMC Nursing, 2021)
Abstract Aims To understand the experiences of nursing students and academic staff of an intervention to decrease burnout and increase retention of early career nurses, in order to identify acceptability and feasibility in a single centre. Background Internationally, retention of nurses is a persistent challenge but there is a dearth of knowledge about the perspectives of stakeholders regarding the acceptability and feasibility of interventions to resolve the issue. This study reports an intervention comprising of mindfulness, psychological skills training and cognitive realignment to prepare participants for early careers as nurses. Methods This is an explanatory sequential mixed methods study, conducted by a UK university and healthcare organisation. Participants were final year pre-registration nursing students (n = 74) and academics (n = 7) involved in the implementation of the intervention. Pre and post measures of acceptability were taken using a questionnaire adapted from the Theoretical Framework of Acceptability. Wilcoxon Signed Ranks test was used to assess change in acceptability over time. Qualitative data from semi-structured interviews, focus groups and field notes were thematically analysed, adhering to COREQ guidelines. Data were collected February to December 2019. Results One hundred and five questionnaires, 12 interviews with students and 2 focus groups engaging 7 academic staff were completed. The intervention was perceived as generally acceptable with significant positive increases in acceptability scores over time. Student nurses perceived the intervention equipped them with skills and experience that offered enduring personal benefit. Challenges related to the practice environment and academic assessment pressures. Reported benefits align with known protective factors against burnout and leaving the profession. Conclusion Planning is needed to embed the intervention into curricula and maximise relationships with placement partners. Evaluating acceptability and feasibility offers new knowledge about the value of the intervention for increasing retention and decreasing burnout for early career nurses. Wider implementation is both feasible and recommended by participants.